2023
DOI: 10.1097/sla.0000000000006009
|View full text |Cite
|
Sign up to set email alerts
|

Propensity-Score Matched Analysis of Three Years Survival of TransCarotid Artery Revascularization Versus Carotid Endarterectomy in the Vascular Quality Initiative Medicare Linked Database

Abstract: Objective: Carotid endarterectomy (CEA) remains the gold standard procedure for carotid revascularization. Transfemoral carotid artery stenting (TFCAS) was introduced as a minimally invasive alternative procedure in patients who are at high risk for surgery. However, TFCAS was associated with increased risk of stroke and death compared to CEA. Summary background data: Transcarotid artery revascularization (TCAR) has outperformed TFCAS in several prior s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…33 In a follow-up study using both VQI and Medicare data, Malas et al found the rate of death at one-year was similar in TCAR and CEA regardless of symptomatic status. 34 Together, these findings may suggest that recent MI should not be a contraindication for TCAR or CEA. Additionally, given that CEA performed better than TFCAS in terms of in-hospital stroke/death and stroke/death/MI, our results suggest that designating pre-operative MI as a highrisk factor for CEA should be re-evaluated.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 91%
“…33 In a follow-up study using both VQI and Medicare data, Malas et al found the rate of death at one-year was similar in TCAR and CEA regardless of symptomatic status. 34 Together, these findings may suggest that recent MI should not be a contraindication for TCAR or CEA. Additionally, given that CEA performed better than TFCAS in terms of in-hospital stroke/death and stroke/death/MI, our results suggest that designating pre-operative MI as a highrisk factor for CEA should be re-evaluated.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 91%